Experimental Investigation of a Continuous Reactor for CO2 Capture and CaCO3 Precipitation - Tiefenthaler, Johannes; Mazzotti, Marco (Frontiers in Chemical Engineering, 2022)
In a climate neutral world, the life cycle green house gas (GHG) emissions of precipitated calcium carbonate (PCC) have to be reduced towards net-zero. Mineral carbonation processes allow to do so by replacing the carbon rich calcium source limestone by carbon free industrial mineral wastes. Various processes have been investigated in literature. They exhibit the benefit of little to no feedstock related emissions and high energy savings due to the avoidance of the CaCO3 calcination step. However, the nature of the process changes significantly, which requires a fundamental understanding of the new mechanisms controlling the process of CO2 absorption and CaCO3 precipitation. Within this work, a CO2 rich gas is contacted with a calcium rich aqueous feed in a continuous reactive crystallizor. The CO2 selectively absorbs and precipitates as either vaterite or calcite. The effect of the liquid and gas feed flow rates, of the feed stoichiometric ratio and of the residence time on key performance indicators, such as the CO2 capture efficiency the CaCO3 precipitation efficiency and the features of the final product, is studied experimentally. As expected, these feed characteristics determine the effective stoichiometric ratio of reactants in the liquid phase, ψ. The particle size increases strongly with ψ; vaterite represents the predominant solid phase at ψ < 1 while otherwise a mix of vaterite and calcite was formed, wheras the latter one accounted for 13% to 90% in mass of crystals collected. Moreover, ψ of about one exhibits the highest CO2 capture efficiency exceeding 80%.